2010
DOI: 10.4061/2010/928541
|View full text |Cite
|
Sign up to set email alerts
|

An Emerging Pulmonary Haemorrhagic Syndrome in Dogs: Similar to the Human Leptospiral Pulmonary Haemorrhagic Syndrome?

Abstract: Severe pulmonary haemorrhage is a rare necropsy finding in dogs but the leptospiral pulmonary haemorrhagic syndrome (LPHS) is a well recognized disease in humans. Here we report a pulmonary haemorrhagic syndrome in dogs that closely resembles the human disease. All 15 dogs had massive, pulmonary haemorrhage affecting all lung lobes while haemorrhage in other organs was minimal. Histologically, pulmonary lesions were characterized by acute, alveolar haemorrhage without identifiable vascular lesions. Seven dogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 28 publications
1
33
2
4
Order By: Relevance
“…Hemolysins, specifically the sphingomyelinases, are implicated in the hemorrhagic complications associated with leptospirosis [Alexander et al, 1956;Klopfleisch et al, 2010;Miller et al, 1974;Thompson and Manktelow, 1989]. Studies have demonstrated the hemolytic, poreforming and enzymatic activities of these molecules [Bernheimer and Bey, 1986;Kasarov, 1970;Lee et al, 2000;Lee et al, 2002;Segers et al, 1990; Thompson and Marshall, 1986].…”
mentioning
confidence: 99%
“…Hemolysins, specifically the sphingomyelinases, are implicated in the hemorrhagic complications associated with leptospirosis [Alexander et al, 1956;Klopfleisch et al, 2010;Miller et al, 1974;Thompson and Manktelow, 1989]. Studies have demonstrated the hemolytic, poreforming and enzymatic activities of these molecules [Bernheimer and Bey, 1986;Kasarov, 1970;Lee et al, 2000;Lee et al, 2002;Segers et al, 1990; Thompson and Marshall, 1986].…”
mentioning
confidence: 99%
“…The polymerase chain reaction did not amplify leptospiral DNA in lung tissue, most likely due to presence of a reduced number of the bacteria in the lung, as has been observed in dog models (Klopfleisch et al 2010). Under these circumstances, the pulmonary lesions could be caused by leptospiral toxins produced in distant organs, such as the liver (Miller et al 1974).…”
Section: Discussionmentioning
confidence: 80%
“…The finding that fewer alveolar cells were stained with TTF-1 during inflammation suggests that leptospires cause the injury of ATII cells when they leave the blood vessels to enter the pulmonary interstitium, leading to fewer of ATII cells. It is known that in humans (Croda et al 2010) and canines (Klopfleisch et al 2010), leptospirosis induce extensive necrosis of ATII cells when compared to uninfected controls. Other studies have shown that pathogenic Leptospira can reach the lung interstitium, causing reduced synthesis of endothelial cell cytoskeletal proteins, thus damaging the cells (Martinez--Lopez et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Control tissues (Groups 2 and 3) were retrieved from the tissue collection of the Pathobiology section of University College Dublin. The histopathologic findings of the lungs from the Berlin cohort of dogs have previously been reported [29]. Only the immunohistochemistry findings of these tissues are included in this present study.…”
Section: Animalsmentioning
confidence: 98%
“…Based on the available evidence, it is likely that LPHS is multifactorial and that host and pathogen-related factors affect pathogenesis [24]. Histopathological features of LPHS have been described in acute leptospiral infections in humans [23,25], in several experimental animal models including guinea pigs [9,18], hamsters [26,27] and marmoset monkeys [28], and in a cohort of naturally infected dogs [29]. LPHS is characterised by various degrees of intra-alveolar haemorrhage in the absence of a marked inflammatory cell infiltrate or vasculitis [9,18,25].…”
Section: Introductionmentioning
confidence: 97%